A legendary history in Witihama, Eastern Adonara, Indonesia : an enduring context for disagreement - Barnes, R (Institut de Recherche sur le Sud-Est Asiatique, 2007)
An anthropological literature dealing with conflict such as has afflicted Indonesia in recent years is beginning to emerge. The present article is one of a series dealing with different incidents and forms of conflict and violence in a region of eastern Indonesia. It furthers a discussion on contested claims for precedence. Such claims in Indonesia are often made by means of legends of origin. Descent groups claiming outside origin may, nevertheless, demand political power from those claiming to be autochthonous. The latter may or not concede these functions to others, but they commonly assert a mystical authority based on local origin. In Witihama, eastern Adonara, two branches of Lama Tokan clan dispute their relative status. One, which has long provided political leadership, claims to have originated in the Moluccas. The other, which attempts to preserve its mystical authority, deems itself to have originated at the top of the Boleng volcano, but its autochthonous origin is disputed by others. This particular dispute has parallels elsewhere. Unlike other incidents in the past, it seems both peaceable and permanent. Une littérature anthropologique sur le conflit, tels ceux qui ont endeuillé l'Indonésie ces dernières années, commence à se constituer. Cet article fait partie d'une série d'articles sur divers incidents et sur les formes de conflit et de violence dans une région de l'Indonésie orientale. Il poursuit un débat sur les revendications contestées d'antériorité. En Indonésie, ces revendications sont souvent fondées sur des légendes d'origines. Des groupes de descendance se réclamant d'origines étrangères peuvent cependant exiger le pouvoir politique de ceux se réclamant d'origines authochtones. Ces derniers peuvent ou non concéder ces fonctions, mais généralement affirment leur autorité mystique, fondée sur leurs origines locales. A Witihama (ile d'Adonara orientale), deux branches du clan Lama Tokan sont en désaccord sur leur statut relatif. L'une, qui a longtemps fourni les chefs politiques, prétend être originaire des Moloques. L'autre, qui tente de préserver son autorité mystique, se considère originaire du sommet du volcan Boleng, mais ces origines autochtones sont contestées par d'autres. Cette dissension particulière, qui trouve des parallèles ailleurs, semble à la fois pacifique et permanente, contrairement à d'autres incidents passés.